SERVICE QUALITY AND IMAGE ON HOTEL CUSTOMER LOYALTY: (MEDIATION OF CUSTOMER’S TRUST) - Puspaningtyas, Meinarti; Armanu; Hadiwidjojo, Djumilah; Djumahir (International Journal of Psychosocial Rehabilitation, 2020)
Abstract. The purpose of this study is to obtain empirical evidence of the effect of service quality and hotel image on customer trust and loyalty and to obtain empirical evidence of trust mediating the effect of service quality and hotel image on customer loyalty. This research was conducted on Santika hotel customers, Best Western OJ Hotels, Ultima Horison Malang Hotels, Atria Hotels & Conferences, Harris Hotels & Conventions and Aria Gajayana Hotels with 160 customers. Analysis of the data used in this study is the analysis of the data used in this study is the Structural Equation Modeling. The results showed that 4-star hotel customers in Malang will have high trust and loyalty towards the hotel if the quality of service and image of the hotel can be enjoyed by hotel customers. Increasing customer loyalty of 4-star hotels in Malang due to the role of trust and customer trust can mediate the influence of service quality and hotel image on customer loyalty of 4-star hotels in Malang.